A prospective study on emerging roles of phytoalexins in plant protection - PARJANYA KUMAR SHUKLA; PRAGYA MISHRA; NEHA MISHRA (International Journal of Pharma and Bio Sciences, 2019)
Previous extensive literature describes the negative impact of phytoalexins as exhibiting in vitro toxicity across much of the biological spectrum, prokaryotic and eukaryotic organisms. However, recent researches has been demonstrated that phytoalexins may also display health-promoting effects on overall health and longevity of humans which take away the attention of scientist and researchers to explore its beneficial aspects. Inducible plant defense responses consist of low molecular weight antimicrobial compounds called phytoalexins, produced by plants as a response to biotic and abiotic stresses which most prominently includes the pathogenic attack. The antimicrobial properties of phytoalexins advise that they are significant component of plant defense as such they participate in an important role in an intricate defense system enable plants to organize invading microorganisms. In this review, we detail some of the popularly known phytoalexins with their chemical structure produced by a range of crop plants belonging to the family Brassicaceae, Vitaceae, Solanaceae Fabaceae, and Poaceae, Malvaceae, Orchidaceae, Piperaceae, Rosaceae, Rutaceae etc. Studies on usual distinction in phytoalexin production and the accretion of phytoalexins beneath field conditions may be accessible as another means of evaluating the task of these compounds in resistance to pathogens and other pests. Phytoalexins are natural toxic substances against microorganisms and they show deadly effects for the animals and for the plant itself, produced de novo in plants as a defensive response against microbial infection. In this review the key characteristics of this diverse cluster of molecules, specifically their chemical structures, regulation mechanisms, biosynthesis, biological activities, metabolism and molecular engineering. Hence, we have done an attempt to shed some light on crucial aspects that require further study includinf clinical and molecular aspects to determine effective physiological concentrations. This may further help to explore the real impact of these wide array of phytoalexins in preserving the plant’s health; produced as an defensive response against the resultant of attack by different pathogen.